Graphing Functions of Two Variables in Spreadsheets - Jan Benacka (Spreadsheets in Education, 2011)
A method of graphing functions of two variables in spreadsheets is presented. The method uses parallel orthogonal projection. The xyz coordinate system is revolvable in two planes so the graph can be viewed from any direction. The graph is constructed as a mesh made over the rectangle [xmin, xmax] x [ymin, ymax] in the x and y directions. Graphing discontinuous functions are also shown. The visibility problem, that is, the problem of overlapping, is not solved.